Formation of bimetallic metal–organic framework nanosheets and their derived porous nickel–cobalt sulfides for supercapacitors - Chen, Chen; Wu, Meng-Ke; Tao, Kai; Zhou, Jiao-Jiao; Li, Yan-Li; Han, Xue; Han, Lei (Dalton transactions : an international journal of inorganic chemistry, 2018)
Metal–organic frameworks (MOFs) show great advantages as new kinds of active materials for energy storage. In this study, bimetallic metal–organic frameworks (Ni/Co-MOFs) with nanosheet-assembled flower-like structures were synthesized by etching Ni-MOF microspheres in a cobalt nitrate solution. It can be clearly observed that the amount of Co(NO 3 ) 2 and etching time play crucial roles in the formation of Ni/Co-MOF nanosheets. The Ni/Co-MOFs were used as electrode materials for supercapacitors and the optimized Ni/Co-MOF-5 exhibited the highest capacitances of 1220.2 F g −1 and 986.7 F g −1 at current densities of 1 A g −1 and 10 A g −1 , respectively. Ni/Co-MOF-5 was further sulfurized, and the derived Ni–Co–S electrode showed a higher specific capacitance of 1377.5 F g −1 at a current density of 1 A g −1 and a retention of 89.4% when the current density was increased to 10 A g −1 , indicating superior rate capability. Furthermore, Ni/Co-MOF-5 and Ni–Co–S showed excellent cycling stability, i.e. about 87.8% and 93.7% of initial capacitance can be still maintained after 3000 cycles of charge–discharge. More interestingly, the Ni/Co-MOF-5//AC ASC shows an energy density of 30.9 W h kg −1 at a power density of 1132.8 W kg −1 , and the Ni–Co–S//AC ASC displays a high energy density of 36.9 W h kg −1 at a power density of 1066.42 W kg −1 . These results demonstrate that the as-synthesized bimetallic Ni/Co-MOF nanosheets and their derived nickel–cobalt sulfides have promising applications in electrochemical supercapacitors.